Visible-light-driven C(sp2)–H arylation of phenols with arylbromides enabled by electron donor–acceptor excitation. Issue 22 (25th February 2022) - Zhu, Da-Liang; Jiang, Shan; Young, David James; Wu, Qi; Li, Hai-Yan; Li, Hong-Xi
Abstract : We herein reported an efficient, catalyst-free, and visible-light-induced C(sp 2 )–H arylation of unprotected phenols with aryl bromides enabled by in situ generated electron donor–acceptor complexes. Abstract : We have developed a catalyst-free visible-light-driven C(sp 2 )–H arylation of unprotected phenols with arylbromides to give 2-arylated phenols. This reaction proceeds through the excitation of an electron donor–acceptor complex between a phenolate and an arylbromide, electron transfer, and debrominative C(sp 2 )–C(sp 2 ) coupling.